Determinasi Kesempatan Kerja di Kabupaten Lombok Barat Tahun 2009-2023 - Deny Satriawan; Muhammad Irwan; Luluk Fadliyanti (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Employment opportunities are a crucial indicator in assessing the stability and economic growth of a region. This study aims to analyze the influence of Gross Regional Domestic Product (GRDP), investment, regional minimum wage, and regional government capital expenditure on employment opportunities in West Lombok Regency during the period 2009–2023. A quantitative approach with a correlational design was employed to examine the relationships among variables using secondary data sourced from the Central Statistics Agency (BPS) and relevant institutions. The results indicate that GRDP and investment have a positive and significant effect on the increase in employment opportunities. The growth of GRDP reflects higher production capacity, while investment, both in the form of Domestic Investment (PMDN) and Foreign Investment (PMA), acts as a catalyst for the creation of new jobs. The increase in the minimum wage has a limited impact, suggesting the need to balance labor interests with business capabilities. Meanwhile, regional government capital expenditure allocated for infrastructure and public facilities has been proven to support both direct and indirect job creation. These findings underscore the importance of synergy between fiscal policy, investment, and strengthening the real economic sector in expanding inclusive employment access. This study is expected to serve as a reference for the formulation of regional economic development policies oriented towards enhancing community welfare through the provision of sustainable employment opportunities.